The use of Auditors the Islamic Financial Engineering tool for Assessing Funding Risk Management in Islamic Banks: Applied research on a sample of Islamic banks (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Experience the Islamic financial industry faces many challenges, most notably the lack of proper risk management tools that meet the requirements of legality and economic efficiency advantage from another side, so it requires the search for innovative ways to manage the risk of Islamic banking, Islamic finance industry is manufacture up-to-date, if compared with the financial industry (traditional), which increases the problematic of risk management in the Islamic financial industry nature of treatment which should be compatible with Islamic law, as well as economic efficiency, thereby Progress came the importance of research to highlight the entrance to Islamic financial engineering and the goals sought to be achieved through the use of modern input on risk management in the Islamic financial industry, And propose risk management audit programme according to Islamic financial engineering and approval of Auditors to evaluate the management of financing risks in Islamic banks, concluded that research into a range of conclusions, notably the lack of a mechanism to develop the Islamic financial products Islamic banks research sample banks and adoption of specific funding formulas in years without expansion in granting new financing products, the most important recommendations is the need to adopt a mechanism for development of existing financing products and work to which Islamic financial engineering will This aspect.